(untitled) (Research, Society and Development, 2024)
Oral cancer is a malignant neoplasm that affects various anatomical sites in the head and neck region. Its etiology is multifactorial, with several risk factors influencing its development, including smoking, alcohol consumption, and exposure to solar radiation. Potentially malignant disorders present with distinct clinical manifestations, as they carry a significant risk of progressing to cancer. Oral squamous cell carcinoma is the most common type of oral cancer, accounting for approximately 90% of all malignant tumors in the oral cavity. Therefore, the objective of this study is to present a case of cheiloplasty using the Gillies flap following excisional biopsy in a patient with squamous cell carcinoma. This study is classified as a case report and was conducted in a hospital institution in the Recôncavo region of Bahia, Brazil. The research subject is a male patient, 82 years old, with fair skin, a history of heart disease, kidney disease, diabetes, smoking, and agricultural work with frequent sun exposure, presenting with a lesion on the lower lip that had evolved over approximately two months. The lesion was asymptomatic, with continuous and rapid growth. The procedure performed was an excisional biopsy carried out simultaneously with cheiloplasty, utilizing the Gillies flap technique. The procedure was executed as planned and resulted in excellent postoperative outcomes; the patient experienced appropriate healing, with the preservation of function, anatomy, and aesthetics. This case highlights the importance of accurate diagnosis and treatment planning, as well as the necessity of disseminating information on the topic and promoting self-examination among the general population.